Pola Asuh Orang Tua Tunggal Dalam Membentuk Akhlak Mulia Anak - Sarah Maulida; Mulyadi Mulyadi (Pedir Research Institute, 2021)
Parenting patterns greatly affect the personality and behavior of children as adults and in fact, no parent wants their children to develop and develop with bad morals. In the teachings of Islam, the morality towards parents is strongly emphasized, including the sins of the child against the parents, including major sins that are tormented not only in the hereafter but also in the world. In a single parent family, the dual role of a father and mother is a necessity that cannot be avoided anymore. Single parents can be said to be the backbone of the family who must meet all the needs of their children. The dual role of being both father and mother or vice versa makes single parents sometimes do not have enough time and attention for their children. Departing from this phenomenon, the researcher wants to study a research with a focus on the problem, namely (a) how is the parenting style of single parents in shaping the noble character of children at MI Matholiul Falah, Dungus Village, (b) What are the obstacles found in how single parent parenting is in shaping the noble morals of children at MI Matholiul Falah, Dungus Village. This study uses a qualitative method with a phenomenological study approach. Data collection techniques by observation, interviews, and documentation. The data analysis technique used the analysis of Miles and Huberman. Test the validity of the data by triangulation and reference adequacy. The results showed that there were 2 single parent parenting styles in shaping the noble character of children in MI Matholiul Falah, Dungus Village, namely democratic and authoritarian. While the obstacles found in the parenting style of single parents in shaping the noble character of children at MI Matholiul Falah, Dungus Village, are lack of affection, social and emotional development, lack of communication.